Ionothermal synthesis of novel Pb–OH–Cu–X (X = Cl, Br and I) quaternary heterometallic frameworks with tunable optical properties. Issue 16 (30th March 2017) - Xue, Ying-Ying; Zhang, Li-Xia; Li, Shu-Ni; Jiang, Yu-Cheng; Hu, Man-Cheng; Zhai, Quan-Guo
Abstract : Ionothermal synthesis of novel Pb–OH–Cu–X quaternary heterometallic frameworks exhibiting tunable structures as well as solid-state semiconducting and luminescence properties. Abstract : Reported herein is the new application of ionothermal synthesis for inorganic optical materials. Under ionothermal conditions with different imidazolium ionic liquids, novel quaternary heterometallic frameworks based on [Pb4 (OH)4 ] cubane and [CuCl4 ] or [CuBr4 ] chains and [Cu2 I6 ] binuclear clusters have been successfully produced. Simple chlorine, bromine and iodine replacement leads to not only the space group change (tetragonal I 41/ acd for1 and2, and orthorhombic Fddd for3 ) but also the topological net transformation (8, 12-net for1 and2, and 6, 6-net for3 ). Notably, compounds1, 2 and3 all show tunable solid-state semiconducting and luminescence properties.